Application Of Mike 11 Gis Model For Modeling Of Flood In Sungai Kayu Ara Catchment - Arbai, Sabariah (2002)
Flash flood occurring from fast development and socioeconomic growth within Klang Valley has imposed a huge strain impact onto the entire urbanized areas. Accurate techniques in ascertaining flood estimation and prediction would normally be able to propose beneficial solutions in counteracting the phenomena. However, this would require up to date reliable data and effective hydrological modeling coupled to socio-economic studies. These types of studies is time consuming and costly. Complex models produce large quantities of result and difficult for people without specialized backgrounds to understand . New modeling techniques and computer visualization would improve the timeliness and accuracy of hydrological analysis and flood forecasting. With the limited data, complex hydrological approaches could be accomplished.This study intends to illustrate the capability of MIKE 11 GIS to simulate the flood map for Sungai Kayu Ara in modeling the flood mapping. Direct runoff hydrograph could be generated from the rating curve to be used as the input data in preparing the simulation for the flash flood . Crucial ground survey data as one of the significant criteria in producing reliable flood elevation profile is examined . The study also shows that Geographical Information System (GIS) is capable to integrate spatial data and applying spatial simulation from limited data. It is able assist in the understanding of the flooding physical processes and in facilitating the decision-making . The flood simulation can further be modeled with changes in land-use and curve numbers features pertaining to the future development growth. In achieving the above objective, flood modeling was carried out on Sungai Kayu Ara catchment area. In the process MIKE 11 GIS was used as a database and data processor. The available hydrological (rainfall and water-level) data acquired from the data of 1996 to 1998 , were used to produce the flow simulation during the time of the storm event. This result of the study shows that it is possible to use limited hydrological data to map the flash flood using MIKE 11 and MIKE 11 GIS. However, ground survey data with cross sectional intervals of 75 m to 100 m used in the study was found to be insufficient to provide adequately the elevation profile and further refinement is neccessary.